摆线钢球行星传动中短幅系数取值方法研究 - 蔡峰; 张鹏; 张玉华; 刘东 (Jixie chuandong)
Curtate ratio is important parameters of cycloid ball planetary transmission,its selection directly affects the transmission performance.According to its importance,the selection of curtate ratio is researched.Firstly,considering the comprehensive mechanical properties of the cycloid ball planetary transmission,and setting the range of curtate ratio.Secondly,based on the stress analysis of the meshing pairs,and the stress analysis and geometric constraints of turning arm bearing,with the reliability of turning arm bearing for the principle the method of compute the lower limit of curtate ratio is determined.Then considering the actual conditions of load fluctuation and top cutting running-in of the meshing pair,and taking the strength of meshing pairs of cycloid ball as the foundation,the method to compute the upper limit of curtate ratio is determined.Finally,the range of curtate ratio is given,and the conclusion is verified by the design examples.